Keratitis, povzročen z na meticilin odpornim stafilokokusom avreusom - Godina-Kariž, Stanka (Zdravniški vestnik, 2004)
Background. Bacterial keratitis, because of its high incidence and potential complications, is one of the most sight threatening ocular infections. Methods. We report a case of 72 year-old woman with bacterial keratitis admitted to the ophthalmology department. S. aureus sensitive to methicillin was cultured from the swabs of corneal ulcer. Topical ciprofloxacin and tobramycin eye drops were administered to the treated eyes. On the third day the patient was transferred to the internal department due to an advanced heart failure and worsening renal insufficiency. For a very brief time she washospitalized in the internal intensive care unit. Despite antibiotic therapy keratitis gradually worsened. Repeated corneal cultures revealed S. aureus resistant to methicillin. Treatment with topical vancomycin resulted ingradual regression of inflammation and adequate epithelization of corneal ulcer. Conclusions. S. aureus is an important pathogen associated with bacterial keratitis. Because the incidence of S. aureus resistant to methicillin in hospitals is increasing, the possibility of this infection in hospitalized patients with bacterial keratitis should always be considered.
Keywords: Aged; bakterijske okužbe; bakterijski keratitis; Ciprofloksacin; Ciprofloxacin; Drug Therapy; Keratitis; Methicillin Resistance; Meticilinska rezistenca; Microbial Sensitivity Tests; Mikrobni, občutljivostni testi; očesne bolezni; Stafilokokne infekcije; Staphylococcal Infections; Staphylococcus Aureus; Starostniki; Tobramicin; Tobramycin; Vancomycin; Vankomicin